(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
Emerging markets represent an exceptional opportunity for the pharmaceutical industry. Although a precise definition is not yet available, economists define emerging markets as developing prosperous countries in which investment is expected to result in higher income despite high risks. Qualifying a market as emerging is not merely based on the economic status of the country, but also on several criteria that render the definition applicable to each country.